Population pharmacokinetics of tanezumab following intravenous or subcutaneous administration to patients with osteoarthritis or chronic low back pain. Issue 7 (28th February 2022) - Shoji, Satoshi; Suzuki, Akiyuki; Gaitonde, Puneet; Cai, Chun‐Hua; Marshall, Scott
Abstract : Aims: Describe population pharmacokinetics of intravenous (IV) and subcutaneous (SC) tanezumab across Phase 2b/3 studies of osteoarthritis and chronic low back pain. Methods: Data from 10 studies of IV or SC tanezumab (2.5–20 mg every 8 wk for up to 56 wk) were included in a multistep analysis. In Step 1, a 2‐compartment model with linear and nonlinear elimination (based on prior analysis of pre‐2015 IV osteoarthritis studies) was expanded to include other pre‐2015 studies. In Step 2, post‐2015 SC studies were combined into the model. Steps 3 and 4 evaluated impact of baseline nerve growth factor (NGF) and treatment‐emergent anti‐drug antibodies (TE ADA). Results: SC bioavailability was estimated at 62–76%. The key disposition parameters CL, Vc, Vp and KM were estimated to be 0.133 L d −1, 2.6 L, 1.77 L and 31.2 μg L −1, respectively. Plasma tanezumab concentration was predicted to reach Cmax at 8.9–11.2 days following single and multiple SC administration in typical patients within the dose range of SC Phase 3 studies (2.5–10 mg every 8 wk). Exposure of a typical patient was similar between IV and SC for the second part of the dosing interval (wk 4–8). Covariates selected on the absorption parameters were weight, age, sex and injection site. Baseline NGF had minimal effect on maximum elimination capacity and TE ADA status was associated with slightly higher tanezumab clearance (6–7%). Conclusion: Our model adequately described plasma tanezumab concentration vs . time following IV or SC administration. Weight was the most influential covariate with respect to absorption of tanezumab in comparison to patient population (osteoarthritis and chronic low back pain) or other demographics. There was no clinically relevant effect of baseline NGF or TE ADA on tanezumab PK.